2020
DOI: 10.1111/1755-0998.13170
|View full text |Cite
|
Sign up to set email alerts
|

Identifying error and accurately interpreting environmental DNA metabarcoding results: A case study to detect vertebrates at arid zone waterholes

Abstract: Environmental DNA (eDNA) metabarcoding surveys enable rapid, noninvasive identification of taxa from trace samples with wide‐ranging applications from characterizing local biodiversity to identifying food‐web interactions. However, the technique is prone to error from two major sources: (a) contamination through foreign DNA entering the workflow, and (b) misidentification of DNA within the workflow. Both types of error have the potential to obscure true taxon presence or to increase taxonomic richness by incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 111 publications
0
36
0
Order By: Relevance
“…Future studies should focus on developing, testing, comparing, and improving molecular markers for plants. Specifically, to select for markers that detect spring dependent plant communities (Fazekas et al., 2009) as well as animals (e.g., 16S, Smith et al., 2020; 12S, Furlan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should focus on developing, testing, comparing, and improving molecular markers for plants. Specifically, to select for markers that detect spring dependent plant communities (Fazekas et al., 2009) as well as animals (e.g., 16S, Smith et al., 2020; 12S, Furlan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In eDNA metabarcoding, false positives can occur because of various technical factors, including contamination, amplification or sequencing errors, or tag switching (Zhan & MacIsaac 2015, Furlan et al 2020. As unmodeled false positives can cause a significant bias in the inference of site occupancy (Royle & Link 2006), adequate precautions must be taken in applying the proposed model to an eDNA metabarcoding study.…”
Section: Discussionmentioning
confidence: 99%
“…In eDNA metabarcoding, false positives can occur because of various technical factors, including contamination, amplification or sequencing errors, or tag switching (Zhan & MacIsaac 2015, Furlan et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The low contamination in our laboratory positive and negative controls also verify that contamination from the laboratory, as well as cross contamination among plates and wells, was minimal. Surprisingly few studies report sources of contamination or when it occurred during the process, but Harper et al (2019) found that most contamination occurred during sampling and PCR, and Furlan et al (2020) found that some contamination occurred through all stages of sampling and processing, but mostly during PCR. Because we subtracted the maximum number of reads in controls from all read counts in associated samples, we were confident that the remaining reads were true detections.…”
Section: Discussionmentioning
confidence: 99%